Robust point location estimators for the EWMA control chart. Issue 1 (2nd January 2016) - Zwetsloot, Inez M.; Schoonhoven, Marit; Does, Ronald J. M. M.
Abstract: In practice, the EWMA control chart for process monitoring is based on parameters estimated from a retrospective data set representing the process characteristic under study. This data set may contain contaminated observations, which in turn can affect the estimates and hence the control chart's performance. We study the problem of estimating the location when the data set may or may not contain contaminated observations. We compare six point estimators proposed in the SPC literature. The quality of the estimators is evaluated in terms of estimation accuracy. Moreover, we study the impact of the estimators on the performance of the EWMA control chart based on the different location estimators.